PENGARUH ETIKA DAN SKEPTISME PROFESIONAL TERHADAP KUALITAS AUDIT DENGAN MODERASI TINGKAT PENDIDIKAN - Mega Rianita Kartika; Avincennia Vindy Fitriana (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2025)
Inspectorate is part of the Government Internal Supervision Apparatus which has the main duties and functions of supervision over government administration. The purpose of the audit process is to produce quality audits with one of the indicators being an objective report. The objectivity of the audit report can be obtained when the auditor is able to apply his professional ethics and has a professional skepticism. These two things can be obtained by auditors, one of which is through the level of education. This study was conducted on 85 auditors at the West Java Provincial Inspectorate as respondents with quantitative research methods with descriptive and verifiable approaches. The data source is primary data using questionnaires. The purpose of this study is to determine the influence of ethics and professional skepticism on audit quality both simultaneously and partially, as well as the role of education level as a moderation variable in influencing it. The technical analysis of this study uses Moderated Regression Analysis. The results showed that ethics and professional skepticism had an effect on the quality of audits both simultaneously and partially. The level of education is not able to moderate the influence of ethics and professional skepticism on audit quality.